Altitude Wise Variation in Seedling Characteristics of Picea smithiana (Wall.) Boiss. In Forests of South Kashmir, J & K, India - Singh, Manjeet; Singh, V. R. R.; Zaffar, S. N.; Rahul (Indian Forester, 2018)
The study was carried out in Jammu and Kashmir under four forest divisions (Lidder, Anantnag, Kulgam and Shopian) 0 which falls under three altitudinal zones (<2200m-Lower, 2200-2600m-Middle and >2600m-Upper) (latitude 30°37' to 34 55' N and longitude 74°44' to 75°25' E) relating to seed and seedling characteristics of Picea smithiana which indicated significant variation among seed and seedling parameters. Number of seeds per cone averages at 123 at lower, 173.26 at middle and 98.38 at upper altitudes. Germination study reveals that germination percent at maturity was 28.96 at lower, 42.6 at middle and 19.24 at higher altitude. Germination energy was 18.64 at lower, 23.18 at middle and 10.55 at higher altitude, germination energy index was 35.05 at lower, 41.34 at middle and 31.72 at higher altitude. Seeds of mid altitudes under laboratory conditions showed better performance in terms of hypocotyl length, radical length, number of cotyledons, total seedling length and vigour index. In seedlings raised from seed sources at lower altitude (A1) shows that bud break takes place in the first fortnight of April, in mid altitude (A2) it takes place in second fortnight of April and in higher altitude (A3 altitude) the bud break takes place in first fortnight of May.